Legal Protection of Personal Health Data in Electronic Health Records in Indonesia - Arie Hidayat, Teuku; Gede Andi Kurniawan, Dewa; Lany, Arman (Jurnal Ilmiah Dunia Hukum, 2025)
Digital transformation in Indonesia’s healthcare sector, particularly through Electronic Health Records (EHR), has improved efficiency and accuracy in managing patient data. However, protecting personal health information remains a major challenge. This study aims to analyze data protection within the EHR system in Indonesia, particularly in relation to existing regulations, such as Law Number 17 of 2023 on Health and Law Number 27 of 2022 on Personal Data Protection (PDP Law). Using a juridical normative approach and literature review, the study examines relevant legal documents. The research findings show that although regulations related to data protection are quite comprehensive, their implementation on the ground still faces obstacles such as a lack of legal awareness, infrastructure disparities, and limited human resources in hospitals. Furthermore, there is an overlap of authority between the Ministry of Health and the data protection authority, which could create legal gaps. The study recommends developing more specific regulations, strengthening inter-agency coordination, and enhancing hospital capacity to manage patient data security. While Indonesia has a robust legal framework, improvements in technical implementation, supervision, and hospital preparedness are essential to ensure effective protection of patient data within the EHR system.